2017
DOI: 10.1002/admi.201700172
|View full text |Cite
|
Sign up to set email alerts
|

Local Dielectric Breakdown Path along c‐Axis Planar Boundaries in Cr2O3 Thin Films

Abstract: The 3D atomic structure of an interface‐stabilized planar boundary in the magnetoelectric Cr2O3 thin films is reported based on scanning transmission electron microscopy as a function of scattering angle. Local boundary electron energy loss spectroscopy shows a prepeak on the O–K edge arising from unoccupied O 2p states. Density functional theory calculations reproduce the images and spectra and show that the boundary has smaller bandgap than bulk Cr2O3, but does not interrupt the (0001) surface spin polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…60 nm thick Cr 2 O 3 on V 2 O 3 exhibits a high breakdown field (~ 170 to 225 MV/m- Fig. 2b), which is comparable to previously reported values (200 MV/m) for 500 nm thick Cr 2 O 3 thin films with 200 × 200 μm electrodes 12 , which is ~ 20% of the bulk breakdown field (1,000 MV/m) 16 . These values, however, are 3 × higher than the breakdown fields observed in the Cr 2 O 3 /Pt heterostructures containing twin domains.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…60 nm thick Cr 2 O 3 on V 2 O 3 exhibits a high breakdown field (~ 170 to 225 MV/m- Fig. 2b), which is comparable to previously reported values (200 MV/m) for 500 nm thick Cr 2 O 3 thin films with 200 × 200 μm electrodes 12 , which is ~ 20% of the bulk breakdown field (1,000 MV/m) 16 . These values, however, are 3 × higher than the breakdown fields observed in the Cr 2 O 3 /Pt heterostructures containing twin domains.…”
supporting
confidence: 89%
“…The relatively conductive twin boundaries lead to high leakage current and reduce dielectric breakdown voltage down below the critical magnetoelectric switching voltage. In previous reports, this issue has been circumvented by utilizing Cr 2 O 3 films of large thickness 12,16 but at proposed device scales this is not a viable solution. Using a V 2 O 3 electrode layer, a metallic oxide isostructural with Cr 2 O 3 , has been shown to reduce or even eliminate twin domains and thereby reduce the leakage current of a 300 nm thick Cr 2 O 3 film in comparison with metal electrodes 8,17 .…”
mentioning
confidence: 99%
“…It appears that growing the samples at 500 °C even with an additional post‐annealing at 700 °C (sample #5, Table 1) is insufficient to realize an antiferromagnetic film responding to the field cooling procedure (green curve in Figure 2a). This finding is in line with the recent work by Vu et al., [ 43 ] where it is reported that a good crystallinity is observed for Cr 2 O 3 thin films grown at 700 °C (compare to the properties of thin films prepared at a lower temperature [ 44,45 ] ). While the sample grown at 800 °C (sample #3, Table 1) reveals the strongest change of the transversal resistance (red curve in Figure 2a), the film prepared at 900 °C (sample #4, Table 1, blue curve in Figure 2a) shows the weakest measured transverse resistance change among all samples.…”
Section: Resultssupporting
confidence: 92%
“…Dielectric breakdown in thin-film Cr2O3 occcurs at an electric field of 200 V/µm. 47 to 200 V/µm. 47 Even at a generous magnetic field of 1 T, the ME pressure that can be reached before breakdown is just 525 J/m 3 .…”
Section: Applicationmentioning
confidence: 99%
“…47 to 200 V/µm. 47 Even at a generous magnetic field of 1 T, the ME pressure that can be reached before breakdown is just 525 J/m 3 . Experimental advancements in increasing the breakdown field and reducing the value of the magnetic anisotropy 48 will be needed to realize dynamics in the sub-nanosecond regime.…”
Section: Fig 1 Uniaxial Anisotropy and Sublattice Magnetization Ofmentioning
confidence: 99%